Meningkatkan Motivasi dan Hasil Belajar Siswa dengan Menggunakan Media Digital (YouTube dan Game Online) pada Materi Literasi Digital untuk Kemajuan Bangsa di SMP Sunan Giri Kota Probolinggo - Dzaky Isyuniandri; Alfiatus Syarofah; Halimah Halimah; Indani Khoirun Nisak; Syamriba Ardila (Universitas 45 Surabaya, 2024)
This Classroom Action Research (PTK) was motivated by the low interest of students in Civics subjects. This is thought to be due to a lack of adequate reference sources, which makes students have to write a lot of study material which then makes them feel bored and boring. This Classroom Action Research (PTK) aims to increase student motivation and learning outcomes by using digital media (YouTube and Online Games) on the material